2016
DOI: 10.1136/jim-2016-000166
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of 18F-Fdg Pet/Ct Metabolic, Clinical and Pathological Characteristics of Primary Squamous Cell Carcinoma of the Cervix

Abstract: The objectives of this retrospective study were to use preoperative fluoro-d-glucose (FDG) PET/CT in patients with primary cervical squamous cell carcinoma to explore the relationship between clinical, pathological and metabolic characteristics. Eighty consecutive patients with squamous cell carcinoma of cervix received FDG PET/CT scan before treatment. Metabolic tumor volume (MTV), total lesion glycolysis (TLG) and the peak standardized uptake value (SUVpeak) of the cervical tumors were calculated by an itera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
5
4
0
Order By: Relevance
“…Thus, we analysed the relationship between each PRF and PET/CT parameter in our study. The results showed that all PET/CT parameters, including SUVmax, MTV and TLG, were statistically associated with tumour size and deep stromal invasion, which was consistent with previous studies [ 17 , 18 ]. We also found in PET/CT that parametrial invasion and pelvic lymph node metastasis had significant relationships with MTV and TLG, but not SUVmax, even though magnetic resonance imaging (MRI) is the best technology for evaluating the invasion of the parametrium in uterine cervical cancer.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, we analysed the relationship between each PRF and PET/CT parameter in our study. The results showed that all PET/CT parameters, including SUVmax, MTV and TLG, were statistically associated with tumour size and deep stromal invasion, which was consistent with previous studies [ 17 , 18 ]. We also found in PET/CT that parametrial invasion and pelvic lymph node metastasis had significant relationships with MTV and TLG, but not SUVmax, even though magnetic resonance imaging (MRI) is the best technology for evaluating the invasion of the parametrium in uterine cervical cancer.…”
Section: Discussionsupporting
confidence: 92%
“…3 The relationships between 18 F-FDG uptake and parametria invasion and pelvic lymph node metastasis. For high-risk factor, MTV and TLG had significant relationships with parametria invasion (MTV: p < 0.001; TLG: p < 0.001) and pelvic lymph node metastasis (MTV: p < 0.001; TLG: p = 0.007) CT parameters, including SUVmax, MTV and TLG, were statistically associated with tumour size and deep stromal invasion, which was consistent with previous studies [17,18]. We also found in PET/CT that parametrial invasion and pelvic lymph node metastasis had significant relationships with MTV and TLG, but not SUVmax, even though magnetic resonance imaging (MRI) is the best technology for evaluating the invasion of the parametrium in uterine cervical cancer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We used an iterative adaptive algorithm provided by PET VCAR software that automatically delineated ROIs and generated measurement results, greatly reducing errors of manually delineated ROIs. 17 Nevertheless, we found it interesting that MTV and TLG had higher specificity and lower false positivity than other parameters in identifying EAH and EC. We performed linear regression modeling (lasso) of texture classification to analyze the discriminant ability of texture features extracted from samples.…”
Section: Discussionmentioning
confidence: 66%
“…Disagreements were resolved by consensus through negotiation. The SUVpeak, SUVmax, SUVmean, MTV, and TLG parameters were obtained for each endometrial lesion using the PET VCAR software, and the thresholds of delineating tumor edge and regions of interest (ROI) were determined automatically by iterative adaptive algorithm 17 (Figure 1). The physiological absorption regions (eg, intestinal canal, ureter, blood vessel) were not imaged.…”
Section: Methodsmentioning
confidence: 99%